The Impact of Variations in The Concentration of Wungu Leaf Extract (Graptophyllum Pictum (L.) Griff) Upon The Physical Properties of Sunscreen Spray Preparations - Aktifa, Ana Fadilia; Rahmayanti, Mayu; Amalina, Faidatul (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Sunscreen is applied to the skin to protect it from UV rays. Wungu leaves (Graptophyllum pictum (L.) Griff), which are rich in flavonoids and exhibit antioxidant activity, are one of the substances that can be used to create sunscreen formulations. The purpose of this research is to determine how varying concentrations of wungu leaf extract affect the physical qualities of sunscreen spray formulations. This research method involves extraction, extract assessment (organoleptic, yield, and water content), formulation with different extract concentrations (500 ppm, 1,000 ppm, and 1,500 ppm), and physical evaluation (organoleptic, homogeneity, pH, viscosity, and spraying pattern). Data analysis use linear regression equations in the software Microsoft Excel. All formulations with different extract quantities yielded green, transparent, liquid, homogenous solutions with a pronounced smell of wungu leaf extract. The results of pH and viscosity tests on formulations including diverse extracts satisfied the requirements for topical spray preparations, with pH and viscosity values sequentially dropping (Formulas 1, 2, and 3) with slope values of -0.43 and -4.835, respectively. The results of the spray pattern test indicate an oval to circular spread with increased diameter values in the extract variation and slope values of 0.55, 0.568, 0.6685, and 0.4865 at spraying distances of 3, 5, 10, and 15 cm, respectively. On the basis of the study's findings, it can be inferred that differences in the content of wungu leaf extract have an effect on the physical properties of spray sunscreen formulations, as measured by pH, viscosity, and spray pattern diameter.